Análise crítica de discurso : disputa entre José Serra e Dilma Russeff pela presidência na campanha eleitoral no ano de 2010, 2008. - Silva, Carla Karina Freitas da (2012)
This study aimed to analyze the speeches of presidential Rousseff and Jose Serra during the 2010 elections. We selected three speeches from each of the presidential candidates (one statement and two debates, one of the 1st round and another in the 2nd round) on education in Brazil, seeking to understand the concepts, proposals, justifications of the planned actions of each then presidential candidates regarding education. Analyzed the using some argumentative operators in order to understand this ideology that permeates political discourse. We have seen how the politician draws its positive character while drawing the negative character of the opponent, appealing tone and polyphony inserted in the speech. The theory of critical discourse analysis based this research, from the relationship between text, discursive practice and social practice because it emphasizes the role of some symbolic discourses that reproduce social power such as political discourse. We analyze non-speaking subjects, but discursive subjects, subjects inserted in a particular social situation, a historic place, socially and ideologically marked. During analyzes, we realized that the then presidential candidate Rousseff always emphasized the actions of the current president Lula as Lula was present in Dilma. This is a persuasive strategy, because the popularity of Lula praised Dilma. But in other statements, the candidate is contradicted by criticizing some negative points of the Lula government to expand the number of fans. Ever the presidential candidate Jose Serra did not mention the name of former president Fernando Henrique due to its low popularity in relation to Lula. This reference would minimize the image himself. Serra appealed to the very emotional and did it very well because this is a characteristic of neoliberalism. Dilma presented a broader view and the real in relation to education. While Serra fled a bit of reality, having a fragmented view of education, emphasizing his proposals for technical education